BACTERIOLOGICAL ANALYSIS OF CATFISH (Clarias gariepinus) IN OWO AREA, ONDO STATE, NIGERIA - A.O, Egbebi; A.A, Muhammad; M., Ugbodaga; M.O, Oyama (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A total of eight catfish (Clarias gariepinus) were collected from different fishponds inIyere and Otapete areas of Owo local government in Ondo State. The skin, gills, andintestines of the fish were investigated for presence of bacteria. The species of bacteriaisolated from the fish samples and their percentage occurrence include Serratia spp.(2%), Salmonella spp. (32%), Escherichia coli (24%), Proteus spp. (3%), Enterococcusspp. (7%), Staphylococcus spp. (9%), Streptococcus spp. (9%), Klebsiella spp. (3%),Bacillus spp. (6%) and Pseudomonas spp. (5%). The highest microbial count (total viablecount) from Clarias gariepinus was 6.5 x 102 CFU/ml from skin samples, 3.5 x 107CFU/ml from gill samples, and 4.5 x 102 CFU/ml from intestine samples.Correspondingly, the highest microbial count (total coliform count) recorded was 7.0 x102 CFU/ml from skin samples, 2.5 x 103 CFU/ml from gill samples, and 3.0 x 101CFU/ml from intestine samples. Finally, the highest microbial count (total anaerobiccount) from Clarias gariepinus was 2.0 x 102 CFU/ml from skin samples, 2.5 x 104CFU/ml from gill samples, and 2.5 x 102 CFU/ml from intestine samples. The occurrenceof such isolated bacteria if not properly checked could endanger both the fish and theultimate consumers particularly if the fish harvested from these farms are undercooked.